Rituximab in patients with membranous nephropathy and kidney insufficiency - Yanhong Guo; Liuwei Wang; Yulin Wang; Xiaodan Li; Zihan Zhai; Lu Yu; Yan Liang; Peipei Liu; Lin Tang (Frontiers Media S.A., 2022)
Introduction: Patients with membranous nephropathy and kidney insufficiency have an extremely high risk of progression to end-stage renal disease. Whether rituximab can effectively treat membranous nephropathy patients with renal dysfunction remains unknown at present. The aim of our study was to evaluate the effectiveness and safety of rituximab (RTX) in membranous nephropathy with kidney insufficiency.Methods: We retrospectively analyzed the clinical data of 35 membranous nephropathy patients with kidney insufficiency administered in the First Affiliated Hospital of Zhengzhou University between January 2020 and December 2021. Patients were followed every 1-3 months for a total of 6 months. Clinical data were collected including anti-phospholipase A2 receptor antibody (anti-PLA2R antibody) quantification, 24-h urinary protein, serum albumin, and serum creatinine. The percentage of patients who achieved clinical remission was measured.Results: There were 7 (20%) patients who achieved complete or partial response at 6 months after RTX treatment. After 6 months of treatment, patients were clinically improved as evidenced by significant improvements in anti- PLA2R antibody titer [7.70 (5.72, 16.72) vs. 59.20 (17.70, 187.50) RU/ml, p < 0.001], 24-h urine protein [7.04 (4.43, 8.90) vs. 10.15 (4.83, 13.57) g/d, p < 0.001], serum albumin [30.55 (24.97, 33.27) vs. 21.40 (16.75, 25.00)g/L, p < 0.001], serum creatinine [99.50 (75.25, 140.25) vs. 152.00 (134.50, 232.50) µmol/L, p = 0.022], and estimated glomerular filtration rate (eGFR) [78.29 (50.15, 101.55) vs. 41.12 (26.53, 51.41) ml/min/1.73 m2, p = 0.045]. There were no significantly differences between responders and nonresponders in the baseline levels of anti-PLA2R antibodies, proteinuria, serum albumin, and renal function. After the RTX treatment, anti-PLA2R antibodies turned negative in all responders, but the antibody level persisted maintained positive in all but 5 nonresponders. The patients who achieved response maintained a stable kidney function during the study period, with eGFR 29.03 (28.76, 35.07) ml/min/1.73 m2 before rituximab treatment and 62.73 (62.34, 63.13) ml/min/1.73 m2 at the end of follow-up (p = 0.053).Conclusion: RTX therapy might be an alternative treatment in reducing proteinuria and maintaining stable renal function among membranous nephropathy patients even with kidney insufficiency.